One‐Pot Synthesis of Aryl‐ and Alkyl S‐Perfluoroalkylated NH‐Sulfoximines from Sulfides. Issue 64 (24th October 2018) - Chaabouni, Slim; Lohier, Jean‐François; Barthelemy, Anne‐Laure; Glachet, Thomas; Anselmi, Elsa; Dagousset, Guillaume; Diter, Patrick; Pégot, Bruce; Magnier, Emmanuel; Reboul, Vincent
Abstract: A general efficient one‐pot synthesis of S ‐perfluoroalkylated NH ‐sulfoximines from sulfides has been developed using phenyliodine diacetate (PIDA) and ammonium carbamate. Remarkable rate enhancement with trifluoroethanol was observed, presumably due to H‐bonding effects. These mild and metal‐free conditions are compatible with ‐CH2 F, ‐CFCl2, ‐CF2 H, ‐CF2 Br, ‐C4 F9, and ‐CF3 groups, in both the alkyl‐ and aryl series. Based on a 19 F NMR analysis, a λ 6 ‐acetoxysulfanenitrile intermediate was proposed. Abstract : A one‐pot synthesis of S ‐perfluoroalkylated NH ‐sulfoximines from sulfides was developed using phenyliodine diacetate (PIDA) and ammonium carbamate. Remarkable rate enhancement with trifluoroethanol was observed, possibly due to H‐bonding effects. Based on 19 F NMR analysis, a λ 6 ‐acetoxysulfanenitrile intermediate was proposed.